Incidence of anti‐D alloimmunization in D‐negative individuals receiving D‐positive red blood cell transfusion: A systematic review and meta‐analysis. Issue 5 (10th January 2022) - Ji, Yanli; Luo, Guangping; Fu, Yongshui
Abstract: Background and Objectives: The transfusion of D‐negative red blood cells (RBCs) to D‐negative patients has been widely adopted to prevent anti‐D alloimmunization, especially in women of childbearing age. Still, transfusion of D‐positive RBCs to D‐negative recipients is occasionally inevitable in practice, and the resulting incidence of anti‐D in different D‐negative groups of patients has not been well summarized. Materials and Methods: We searched the relevant literature using PubMed, Cochrane Library, and Embase databases from inception date to 30 September 2021. We looked for studies of anti‐D occurring in D‐negative recipients who received D‐positive RBC transfusions. The anti‐D incidence was summarized with 95% confidence intervals (CIs). Data with similar characteristics were combined using a random‐effects model. Results: About 42 studies (2226 cases), which found anti‐D, the exact volume of D‐positive RBC transfused, and the follow‐up time for anti‐D detection, met the inclusion criteria. The pooled anti‐D incidence was 64% (95% CI, range 55%–74%) in volunteers receiving small volumes of D‐positive RBCs, 84% (95% CI, 74%–94%) in those receiving whole units, 26% (95% CI, 19%–32%) in mixed patients, 12% (95% CI, 8%–16%) in oncology patients, 27% (95% CI, 13%–40%) in trauma patients, 4% (95% CI, 0%–8%) in immune‐compromised transplant patients, and 6% (95% CI, 1%–39%) in those with AIDS. Conclusion: Compared with the high frequency of anti‐D in healthy D‐negative volunteers given D‐positive RBCs, we found a lower rate of anti‐D immunization in various D‐negative patients and almost none in transplant and AIDS patients.